Analisis Faktor-Faktor UTAUT dan Trust Terhadap Behavioral Intention Pengguna BNI Mobile Banking Pada Pekerja Migran Indonesia - Rita Rita; Mita Handra Fitria (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2021)
The purpose of this study is to analyze the UTAUT and Trust factors on the Behavioral Intention of BNI mobile banking users on Indonesian Migrant Workers. Performance expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, and Trust as independent variables, Behavioral intention as the dependent variable, and Gender and Age as moderators in this study. The sampling technique used in this study is a side probability as a sampling method. Where probability sampling in this study provides equal opportunities for each element in the population to be selected. Researchers used simple random sampling where the distribution of samples was carried out randomly within the population and each member had the same opportunity. Data collection was carried out by distributing survey questionnaires which were filled in by 100 Indonesian Migrant Workers' participants. The analysis tool used is Smart PLS 3.3.2. The results showed that Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, and Trust towards the Behavioral intention of BNI Mobile banking users to Indonesian Migrant Workers simultaneously. Meanwhile, partially there is an influence on the Facilitating conditions variable on the Behavioral intention of BNI Mobile banking users for Indonesian Migrant Workers, but there is no influence on Performance expectancy, Effort Expectancy, Social Influence, and Trust on the Behavioral intention of BNI Mobile banking users for Indonesian Migrant Workers. There is no influence of the Gender and Age variables in moderating the effect of the Facilitating conditions variable on the Behavioral intention of BNI Mobile banking users to Indonesian Migrant Workers.